Remote but not ready: auditing realities in Malaysia and Thailand - Ahmad @ Muhammad, Norizam; Abd. Wahab, Fasuriah; Sutjasen, Arthit (Faculty of Accountancy, 2025)
When the COVID-19 pandemic hit, it did not just disrupt everyday life, it completely reshaped how work was done across almost every profession. For auditors, who are used to being physically present at client sites, checking inventory in person, and meeting face-to-face, the shift to remote auditing was especially challenging. Many auditors simply were not ready to work from home, even when their firms had provided the necessary systems. As a result, many auditors struggled with confidence and teamwork, especially in unfamiliar virtual environments (Kamaruddin & Hanefah, 2023). In Malaysia and Thailand, responses to these challenges took different forms, offering valuable insights into preparedness and regulatory foresight.